ANALISIS PENGARUH LIKUIDITAS, PROFITABILITAS, LEVERAGE, OPERATING CAPACITY, DAN BIAYA AGENSI MANAJERIAL TERHADAP FINANCIAL DISTRESS - Pawitri, Arsinda Inggar; Alteza, Muniya (Jurnal Fokus Manajemen Bisnis, 2020)
The aim of this study was to determine the effect of liquidity, profitability, leverage, operating capacity, and managerial agency costs on financial distress in manufacturing companies listed on Indonesia Stock Exchange. The research period used was 2015-2017. The type of this research was associative causal with quantitative approach. The population of this study includes all manufacturing companies listed on Indonesia Stock Exchange. The sampling technique used was purposive sampling, and obtained as many as 84 companies, consists of 42 companies that experienced financial distress, and 42 companies that didn’t experience financial distress as comparison company. Data analysis conducted through logistic regression. Based on this research, it was concluded that liquidity proxied by current ratio had no effect to financial distress. Profitability proxied by return on asset had no effect on financial distress. Leverage proxied by debt to asset ratio had a significant and possitiveeffect on financial distress. Operating capacity proxied with total asset turnover had no effect on financial distress. Managerial Agency costs had no effect on financial distress. The Nagelkerke R Square’s score in this study was 0.491 which means that the ability of liquidity, profitability, leverage, operating capacity, and managerial agency were able to explain the variable of financial distress condition by 49.1%. The remaining of 50.9% dependent variables were explained by other factors outside the model.